Asas Kepentingan Terbaik bagi Anak sebagai Dasar Penetapan Hak Asuh Anak di Bawah Umur pada Putusan Nomor 982/Pdt.G/2024/PN.Mdn - Lintang Kinanti Ramafuri; Diana Tantri Cahyaningsih (Indonesian Publication Center, 2026)
This study aims to analyze the legal basis for granting child custody to the father and the application of the principle of the best interests of the child by the judge in Decision No. 982/Pdt.G/2024/PN.Mdn. The study employs a normative legal method using a statutory approach and a case-based approach, supported by primary and secondary data analyzed through legal syllogisms using deductive reasoning. The study findings indicate that the granting of custody to the father is based on the revocation of the mother’s custody rights due to proven neglect, which has a negative impact on the child’s health and development. The principle of the best interests of the child is applied through a comprehensive assessment of both parents’ parenting capacity and maturity, which concluded that the father is better able to ensure the child’s best interests, while visitation rights are still granted to the mother to maintain the child’s psychological well-being. This ruling also reflects the fact that child protection in the legal sphere requires an integrated approach that simultaneously combines legal norms, trial evidence, and an understanding of the child’s psychological needs.